Identification and analysis of educational needs for naval architects and marine engineers in relation to the foreseen context of Maritime Autonomous Surface Ships (MASS) - Bolbot Victor; Methlouthi Oussama; Chaal Meriam; Valdez Osiris; BahooToroody Ahmad; Tsetkova Anastasia; Hellström Magnus; Saarni Jouni; Virtanen Seppo; Owen Douglas; Lei Du; Basnet Sunil (Aalto University School of Engineering, 2025)
We are enduring the introduction of rapid digitalization, smart technologies, and digital connectivity in all industrial domains including maritime under the scope of the industry 4.0 revolution. At the same time, a plethora of challenges need to be faced during this digital transition in the maritime cluster targeting the maritime autonomous surface ships (MASS). Therefore, this report aims at a holistic analysis and identification of the educational needs and competencies required in the maritime domain by the naval architects and marine engineers in relation to MASS and at deriving recommendations for the study program in relation to MASS at Finnish Universities (Aalto University, Abo Akademi University and the University of Turku). To identify current and future education needs, first, the technologies that are/can be employed on MASS have been specified. Then the impact of MASS on the various maritime organisations and job skills has been identified. The study programs offered at other universities in Finland and internationally in relation to MASS have been additionally analysed. Based on the analysis results, recommendations for the study program have been derived. Agile framework to keep Finnish university programs corresponding with the maritime industry needs was also proposed. The analysis results have demonstrated that an increased number of systems employing information and communication technologies will be employed on MASS. The new systems development will increase the demand for maritime professionals who are proficient both in the realm of maritime and computer engineering. Some occupations will remain largely unaffected such as hydrodynamic and structural experts, whilst some others will be slightly altered, such as the jobs of ship designer. Several jobs will be burdened with additional required skill sets, such as the jobs of ship managers. New job types such as remote pilots and surveyors, and maritime cybersecurity experts will also emerge. Universities in Finland and globally have responded to the new demands by either updating their study programs or by providing dedicated master's programs, alone or in cooperation with other universities. They have included courses on advanced robotics or artificial intelligence in their study curriculum along with many others.The investigated universities (Aalto University, Abo Akademi University and the University of Turku) offered courses already include MASS as part of their course's material. However, this material needs to be enhanced by including more aspects in relation to the systems being installed on MASS, digital twins, design challenges associated with MASS, and machine learning techniques used in maritime and maritime cybersecurity.To keep up with the developments in the maritime, it is recommended to organise small biannual workshops in cooperation with industry which can be used to update the study curriculum.